Game theoretical approach for a fair and effective pricing strategy in cloud computing. (27th May 2021) - Temghart, Abdelkarim Ait; Omar, Driss Ait; Baslam, Mohamed; Marwan, Mbarek
The most proven pricing models for the healthy competition are based on game theory techniques that ensure equal consideration of interests for both clients and providers. However, user's preferences and price's sensitivity have a direct influence on the acceptance of new services, an issue that has been relatively neglected by previous research in this area. Thus, we formulate a mathematical model that takes into consideration users' behaviour and at the same time increases the marginal profit. The objective of this work is to improve the revenue for cloud providers as well as users' satisfaction. Experimental results show that the proposed approach is an optimal solution to obtain a reasonable price strategy in a competitive cloud market. More importantly, client's satisfaction has a considerable influence on pricing policy and the expected payoff. In this context, cloud providers compete with each other to maximise their expected utility even when they offer services at a reasonable price.